Perypetie z leksyką Septuaginty - Popowski, Remigiusz (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2008)
The Septuagint is a translation of Hebrew books of the Old Testament by Hellenised Jews in the area of Egypt (Alexandria) from ca. 250 till the end of the 2nd century B.C. It also contains several books in Greek and its text went through several revisions. The most valuable manuscripts of the Septuagint are Codex Vaticanus, Codex Sinaiticus and Codex Alexandrinus (4th and 5th centuries AD). Its edition with the New Testament was published in Venice by Aldus Manutius' press in 1518 but then the carefully prepared in Spain in six volumes Biblia Complutensis was awaiting Papal approval for a year. Apart from the Hebrew, Aramaic, Latin (Vulgate) versions it also contained the Greek version of the Septuagint. The frst Greek dictionary for the Septuagint was compiled by J.C. Biel in 1732–1740 (printed in the Hague, 1779–1780). J.F. Schleusner based on it (Leipzig 1784–1786) as did C.G. Bretschneider (Leipzig 1805). Later there were other attempts to compile such a dictionary, but to no effect. Only at the end of the 20th century two studies appeared independent of each other. One of them was prepared by F. Rehkopf (Göttingen 1989) and the other by J. Lust, E. Eynikel, K. Hauspie (1st edition Stuttgart 1992–1996). The vocabulary of the Septuagint causes much diffculty to lexicographers. First of all, it is a vocabulary of a translation not of the original works and is used in books (within the Septuagint), translated by various authors and at different periods of time and it was submitted to changes in later studies of the text (especially of Origenes), the translators' command of both the language of the original and that of the translation differed. For these and other reasons the lexis of the Septuagint contains, among other things, transliterations of Greek words, numerous neologisms, even more numerous neosemantisms, and it is also woven into the intricate syntax which is often incomprehensible. Thus a lexicographer faces a problem whether to defne words on the basis of the Hebrew substrate or to maintain their hitherto semantics as evidenced in the Greek classical and hellenistic literature. None of the hitherto compiled Greek dictionaries of the Septuagint is a fully capable tool for its effcient translation into any modern languages.
Trials and tribulations with the lexis of the Septuagint
Keywords: Septuagint; Greek lexicography; Greek dictionaries for the Septuagint; Septuagint lexis